Drivers of wood‐inhabiting fungal diversity in European and Oriental beech forests - Giorgi Mamadashvili; Antoine Brin; Maksym Chumak; Valeriia Diedus; Lars Drössler; Bernhard Förster; Kostadin B. Georgiev; Tigran Ghrejyan; Ruslan Hleb; Mark Kalashian; Ivan Kamburov; Gayane Karagyan; et al. (Ecology and Evolution)
Abstract The hyperdiverse wood‐inhabiting fungi play a crucial role in the global carbon cycle, but often are threatened by deadwood removal, particularly in temperate forests dominated by European beech (Fagus sylvatica) and Oriental beech (Fagus orientalis). To study the impact of abiotic drivers, deadwood factors, forest management and biogeographical patterns in forests of both beech species on fungal composition and diversity, we collected 215 deadwood‐drilling samples in 18 forests from France to Armenia and identified fungi by meta‐barcoding. In our analyses, we distinguished the patterns driven by rare, common, and dominant species using Hill numbers. Despite a broad overlap in species, the fungal composition with focus on rare species was determined by Fagus species, deadwood type, deadwood diameter, precipitation, temperature, and management status in decreasing order. Shifting the focus on common and dominant species, only Fagus species, both climate variables and deadwood type remained. The richness of species within the deadwood objects increased significantly only with decay stage. Gamma diversity in European beech forests was higher than in Oriental beech forests. We revealed the highest gamma diversity for old‐growth forests of European beech when focusing on dominant species. Our results implicate that deadwood retention efforts, focusing on dominant fungi species, critical for the decay process, should be distributed across precipitation and temperature gradients and both Fagus species. Strategies focusing on rare species should additionally focus on different diameters and on the conservation of old‐growth forests.